Postpartum care of women with gestational diabetes: survey of healthcare professionals. (November 2015) - Rayanagoudar, Girish; Moore, Misha; Zamora, Javier; Hanson, Philippa; Huda, Mohammed S.B.; Hitman, Graham A.; Thangaratinam, Shakila
Abstract: Objective: To assess the knowledge and practices of healthcare professionals on the postpartum care of women with gestational diabetes. Study design: We surveyed 106 healthcare professionals including obstetricians, diabetologists, general practitioners and midwives in East London and West Midlands in England (September 2014). The questionnaire assessed postpartum screening practices, care provision, future risk and strategies to prevent diabetes in women with gestational diabetes. Results: The response rate was 87% (92/106). Nearly all respondents offered advice on diet (99%; CI 95%, 100%) and exercise (92%; CI 85%, 97%) postnatally in women with diagnosis of gestational diabetes. The preferred screening time for diabetes was 6 weeks to 3 months postpartum (76%; CI 66%, 85%). Overall, oral glucose tolerance test was the preferred test (57%; CI 46%, 67%), although general practitioners preferred fasting glucose (50%; CI 33%, 67%) and glycated hemoglobin (47%; CI 30%, 64%). Most midwives (81%, 17/21) and obstetricians (52%, 11/21) either underestimated or were unsure of the future risk of diabetes. There was lack of consensus on responsibility for immediate postpartum screening. Conclusion: The survey highlights the need for improved awareness of future risk of diabetes in women with gestational diabetes, consensus on optimal postpartum screening and identification of the main healthcare provider responsible for further management. This is particularly important for areas of social deprivation.